Peace talks in the Philippines: Ways out of the impasse - Jasmin Lorch (Stiftung Wissenschaft und Politik (SWP), 2011)
Peace negotiations between the Philippine government and the Moro Islamic LiberationFront (MILF) have reached an impasse. The longer the peace process drags on withoutthe government being able to make the independence movement any substantialconcessions, the greater the risk of fragmentation and radicalisation of the MILF-ledinsurgency in Mindanao. Many of the obstacles to a peace treaty are structural innature however. This includes constitutional hurdles that make it practically impossibleto establish a largely autonomous administrative entity for the Muslim population- the Moros - in Mindanao. These difficulties are compounded by grave deficits inthe Philippine security sector that encourage the activities of private and state-backedmilitias. Constitutional change and security sector reforms are therefore central toending the conflict. So far, Germany and the EU have supported the peace processprimarily through development cooperation. Apart from this, they should also workto promote relevant national reforms and coordinate these with the peace process
Keywords: 320